Clinical value of TAT, PIC and t-PAIC as predictive markers for severe sepsis in pediatric patients - Bai, Huan; Shen, Ling; Zhang, Hailong; Tang, Ning (Frontiers in Pediatrics, 2024)
Objective: Sepsis in pediatric patients can progress to severe sepsis, and identifying biomarkers of this progression may permit timely intervention to prevent it. This study aimed to investigate the ability of thrombin-antithrombin complex (TAT), α2-plasmininhibitor-plasmin complex (PIC) and tissue-type plasminogen activator-inhibitor complex (t-PAIC) to predict severe sepsis in pediatrics early.Methods: 148 eligible pediatric sepsis patients were enrolled in this study, and were then divided into those who progressed to severe sepsis (n=50) or not (n=98). Serum levels of TAT, PIC, and t-PAIC levels were analysed, and simplified pediatric critical illness score (PCIS) and DIC score were calculated on the day of pediatric sepsis diagnosis.Results: Compared with sepsis patients, severe sepsis patients had higher levels of TAT, PIC and t-PAIC. Correlation analysis revealed that TAT, PIC and t-PAIC were significantly correlated with simplified PCIS and DIC score. ROC curve analysis suggested that TAT, PIC and t-PAIC could serve as biomarkers for predicting severe sepsis with the AUC up to 0.862, 0.759 and 0.851, respectively. Stratified analysis demonstrated that the patients with increased levels of TAT, PIC and t-PAIC had worse illness severity and clinical outcome. Univariate logistic regression analysis revealed that TAT, PIC and t-PAIC were all risk factors for severe sepsis, yet only TAT and t-PAIC were independent risk factors in multivariate model.TAT, PIC and t-PAIC could serve as biomarkers for predicting severe sepsis, and correlate with illness severity in pediatrics, what 's more, serum levels of TAT and t-PAIC may be independent risk factors for pediatric severe sepsis.